Pendampingan Izin CPKB Industri Kosmetik Golongan B UMKM CV Bawi Bakena di Kota Palangka Raya - Shesanthi Citrariana; Guntur Satrio Pratomo; Ardi Akbar Tanjung (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2024)
CV Bawi Bakena UMKM is the only herbal cosmetics producer in Palangka Raya City, but has not yet met the legal requirements for the class B cosmetics industry. The aim of this service activity is to provide effective assistance in obtaining a CPKB certificate so that CV Bawi Bakena cosmetics producing UMKM can obtain legality. product. in supporting the micro economy in the city of Palangka Raya. The mentoring model used is the PRA (Participatory Rural Appraisal) approach, where service providers and the community are directly involved in optimizing all existing potential. This service activity uses two stages, namely: the process of repairing building floors and workshops to obtain a class B industrial CPKB permit. The results of the service carried out show progress in fulfilling the submission requirements documents such as the issuance of plan approval from BPOM RI and completeness of production documents for the CPKB permit such as raw material documents, product packaging documents and industrial waste management. Palangka Raya, as a city that has plant biodiversity, has the opportunity to make herbal cosmetics a regional superior product.